Apexification using mineral trioxide aggregate and intracanal post in non-vital upper left lateral incisor - Wisna Darmastuti; Naresworo Apsari; Wignyo Hadriyanto; Tunjung Nugraheni (Faculty of Dentistry, Universitas Gadjah Mada, 2026)
Trauma to young permanent dentitions often occurs. The prevalence of incisor maxillae is quite high. This causes pulp necrosis, which results in dental pulp roots that are not completely formed and apical closure stops. As a result, apex is wide and open. The opening of apex caused by trauma can be coped with apexification. This procedure as first treatment is used for the formation of apical barrier, which can close the apex, before applying gutta-percha. This case report seeks to show the achievement of apex closure in one visit treatment using mineral trioxide aggregate (MTA) in incisor lateral non vital maxillae caused by dental trauma. A 16-year-old male patient admitted to falling from a motorcycle accident 2 months prior. His incisor lateral maxillae left ¾ of its crown, while the orthodontic appliance remained fixed on his teeth. A clinical examination of non-vital teeth used the fracture Ellis IV class with open apex, confirmed with periapical radiograph and CBCT. Apexification in one visit treatment with MTA was performed before a root canal treatment. In the following visit, gutta-percha was cut and fiber post installed, followed by direct resin composite restoration using mock up technique. In conclusion, apexification in one visit treatment using MTA can accelerate treatment with formation of calcium barrier to allow obturation using gutta-percha. This is followed by intracanal retention after treatment to prevent fracture and direct final restoration.